Qualitative and Quantitative Methods to Evaluate Anthocyanins. Issue 5 (21st September 2020) - Teng, Zhaojun; Jiang, Xinwei; He, Fatao; Bai, Weibin
Abstract : Anthocyanins are one of the most important water‐soluble pigments in the nature. Interests in the research of anthocyanins are increasing due to its nutritional value and biological activity. Extraction, separation and qualitative and quantitative analysis of anthocyanins are indispensable and important results in the study of anthocyanins. This article briefly outlines the main extraction processes of anthocyanins, focusing on describing the qualitative and quantitative analysis methods of anthocyanins in details. High performance liquid chromatography and mass spectrometry can be used for qualitative and quantitative analysis. Nuclear magnetic resonance (NMR) spectroscope and other methods such as thin‐layer chromatography, UV–visible spectroscopy and infrared spectrometer can be used for qualitative and analysis. Single pH method, Subtraction method, pH differential method can be used for quantitative and analysis. GRAPHICAL ABSTRACT: